GAMBARAN SUBJCTIVE WELL-BEING SISWA TINGKAT PENDIDIKAN MENENGAH ATAS DI MASA PANDEMI COVID-19 - regina sepriri velarian; Hanifah Hanifah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The COVID-19 pandemic that has occurred around the world has impacted on every level of society. In order to reduce the spread of the COVID-19 virus, the Indonesian Government through the Indonesian Ministry of Education, Culture, Research and Technology (KEMENDIKBUD RISTEK) has imposed the movement of Study From Home or known as Belajar Dari Rumah (BDR), rules for all education participants. BDR itself is something new for Indonesia education system . Learning that was originally done face-to-face was later turned into offline or online distance learning. This changes have an impact on learning participants, such as the subjective well-being of students. This study aims to determine the subjective well-being of students at the High-School level during the COVID 19 period with the implementation of BDR. The study used a mix method approach with a cross-sectional survey design. While the data retrieval using online media in the form of google form. The research participants involved 247 of high school students from 26 schools (SMA/SMK/MA) in Palembang, who were taken with the snowball technique. The measuring instrument uses a three-factor model of Subjective well-being with separate and independent constructs from each other. The research instrument used Satisfaction With Life Scale (SWLS) and Positive and Negative Affect Scale (PANAS). The results showed that life satisfaction (M = 21.17, SD = 5.82) was in the moderate category, positive affect (M = 38.53, SD = 6.36) was in the high category and negative affect was in the moderate category (M = 29.38 SD = 7.61 ) which is in the medium category. It means that the high school students evaluate their experiences and emotions during the COVID-19 pandemic quite positively. This research is expected to be a source of information to support and encourage high school students to be more adaptive and empowered during and post-COVID-19 pandemic.